The Influence of Governance, Leverage and Financial Distress on Profit Management (Case Study at State-Owned Banking Service Companies Listed on the IDX) - Arise Meijulni; Ahmad Soleh; Herlin Herlin (Penerbit Jurnal Indonesia, 2021)
Governance is a series of processes that affect the management and control of a banking service company. Leverage is a source of funds that have fixed costs with the aim of increasing profits. Financial distress is financial difficulty. Profit management is managing income and expenses to get a net profit. The purpose of this study is to identify the influence of governance, leverage, and financial distress on profit management in state-owned companies listed on the Indonesia Stock Exchange (IDX). The technique of collecting data is the most strategic step in research, because the main purpose of research is to get data. The results of this study indicate that the t statistical test shows that governance has a positive and insignificant influence on profit management because the significance value is> 0.05, while leverage and financial distress have a positive and significant influence because the significance value is <0.05.